HUBUNGAN USIA DAN PARITAS IBU DENGAN KEJADIAN PLASENTA PREVIA DI RUMAH SAKIT UMUM DAERAH SITI AISYAH KOTA LUBUKLINGGAU - Putri Andika (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2022)
Placenta previa is a placenta that is abnormally located, that is, in the lower uterine segment that covers part or all of the opening of the birth canal, this bleeding usually occurs at 22 weeks of gestation. The purpose of this study was to study the relationship between maternal age and parity with the incidence of placenta previa at the Siti Aisyah Lubuklinggau Hospital in 2019. This study used an analytical survey method with a case control approach. The population in this study were all maternity women who were recorded in the medical records of the Siti Aisyah Hospital, Lubuklinggau City in 2019 with a total population of 1560 people with 73 people experiencing placenta previa. The samples taken were 146 people using sistematic random sampling. Data collection used is secondary data. Data analysis was performed using univariate and bivariate analysis. Results: of 146 mothers, there were 50 mothers (50%) who had Placenta Previa and did not have Placenta Previa, 97 mothers (66.4%) had age 20-35 years, 90 mothers (61.6%) had multiparity of parity, There is a relationship between age and the incidence of placenta previa and there is a relationship between parity and the incidence of placenta previa. It is hoped that the Siti Aisyah Hospital of Lubuklinggau City can improve services in dealing with placenta previa by providing counseling for pregnant women and prospective pregnant women. Keywords: Placenta Previa, Maternal Age and Maternal Parity